2010
DOI: 10.1007/s00122-010-1511-6
|View full text |Cite
|
Sign up to set email alerts
|

Using a limited mapping strategy to identify major QTLs for resistance to grapevine powdery mildew (Erysiphe necator) and their use in marker-assisted breeding

Abstract: A limited genetic mapping strategy based on simple sequence repeat (SSR) marker data was used with five grape populations segregating for powdery mildew (Erysiphe necator) resistance in an effort to develop genetic markers from multiple sources and enable the pyramiding of resistance loci. Three populations derived their resistance from Muscadinia rotundifolia ‘Magnolia’. The first population (06708) had 97 progeny and was screened with 137 SSR markers from seven chromosomes (4, 7, 9, 12, 13, 15, and 18) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(160 citation statements)
references
References 45 publications
5
152
2
1
Order By: Relevance
“…One region of distortion that stood out was chromosome 15 where all 13 markers showed significant segregation distortion as previously reported for 'Regent' in this region by Welter et al (2007). Riaz et al (2011) also reported segregation distortion for this chromosome in the '06708' population derived from 'Magnolia' (M. rotundifolia). This chromosome appears to be problematic as Lowe and Walker (2006) also could not construct a linkage group 15 for 'Riparia Gloire' (V. riparia), while the map for the other parent, 'Ramsey' (V. champinii), contained four markers spanning a region of 28 cM.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…One region of distortion that stood out was chromosome 15 where all 13 markers showed significant segregation distortion as previously reported for 'Regent' in this region by Welter et al (2007). Riaz et al (2011) also reported segregation distortion for this chromosome in the '06708' population derived from 'Magnolia' (M. rotundifolia). This chromosome appears to be problematic as Lowe and Walker (2006) also could not construct a linkage group 15 for 'Riparia Gloire' (V. riparia), while the map for the other parent, 'Ramsey' (V. champinii), contained four markers spanning a region of 28 cM.…”
Section: Discussionsupporting
confidence: 71%
“…This is higher than that reported by Troggio et al (2007) and Grando et al (2003), but lower than the 40 % reported by Riaz et al (2011). One region of distortion that stood out was chromosome 15 where all 13 markers showed significant segregation distortion as previously reported for 'Regent' in this region by Welter et al (2007).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…For Chromosome 18 the segregation of alleles could easily be defined with five SSR markers. We only find relevance for OIV 94 but other papers show influence in berry weight or size [23] and dependance on the population resistance against Plasmopara [11] or Erysiphe [26].…”
Section: Population 1929 (Grüner Veltliner X Malverina)mentioning
confidence: 81%